Effects of Low Oxygen Levels on Copepod Size Distribution with Depth in Hood Canal - Crouser, Deana (My University, 2019)
Hypoxia is a condition affecting marine trophic webs throughout the world’s oceans. In Hood Canal, Puget Sound is a basin that experiences seasonal hypoxic due to its bathymetry and poor circulation. High primary productivity in this region supports a large secondary trophic level dominated by mesozooplankton. This study looks at how low oxygen levels, affect the size distribution of copepods relative to the oxygen minimum throughout the water column. Samples were collected 19th of August 2017 under normoxic conditions, and the 24th of September 2018 under hypoxic conditions in Twanoh, Hood Canal aboard the R/V Rachel Carson. Multinets were cast at night and during the day to observe diel vertical migration (DVM). Samples were processed in the laboratory and analyzed in excel. Results found oxygen concentrations did not have a significant influence on the copepod size distribution throughout the water column. Population density supported DVM under normoxic conditions and contradicted the theory that copepods use the oxygen minimum layer as predation refuge, under hypoxic conditions.
Keywords: Copepods; Hypoxia; Hood Canal